2014
DOI: 10.1111/ajd.12198
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoporphyria following self‐medication with chlorophyll

Abstract: Two cases of pseudoporphyria are described in which the clinical features of porphyria cutanea tarda occurred in the absence of abnormalities in porphyrin metabolism. Both patients presented with skin fragility and bullae on the dorsal aspect of the hands. The patients consumed a commercial liquid chlorophyll drink in which we detected fluorescent compounds with characteristics typical of previously described chlorophyll derived photosensitisers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…In Australia, chlorophyll is marketed by several vitamin companies as a natural super antioxidant food supplement. This chlorophyll has been reported as a known trigger for pseudoporyphyria [14,16,17]. The lemon water which the patient ingested may contain pheophorbide-a which may be responsible for the outbreaks Another possible trigger for our patient's PP is the use of naproxen for pain relief [18].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In Australia, chlorophyll is marketed by several vitamin companies as a natural super antioxidant food supplement. This chlorophyll has been reported as a known trigger for pseudoporyphyria [14,16,17]. The lemon water which the patient ingested may contain pheophorbide-a which may be responsible for the outbreaks Another possible trigger for our patient's PP is the use of naproxen for pain relief [18].…”
Section: Discussionmentioning
confidence: 89%
“…Chlorophyll-derived photosensitization has been found in ruminant livestock and photosensitizing metabolites such as pheophorbide-a and phytoporphyrin. It has also have been demonstrated in Japanese patients who were self-medicating with commercial extracts of Chlorella algae [14]. Furthermore, in previous studies, researchers have found a substance called pheophorbide-a that results from the chemical procedures used to extract the chlorophyll from the plant.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…4 The second series was an Australian report of two chlorophyll-induced pseudoporphyria cases. 5 In both series, symptoms resolved following chlorophyll cessation. Animal studies have shown that the chlorophyll metabolites pheophorbide-a, pyropheophorbide-a and phytoporphyrin may be responsible for its photosensitivity.…”
Section: Editormentioning
confidence: 90%
“…Zhao, 1,2 J.W. Frew, 2,3 J. Muhaidat, 4 K. Cheung, 4 P. Lee, 5 V. Poulos, 6 I. McCrossin, 7 A.R. Cachia, 3 F. Tefany, 3,8 Tattooing may cause lifethreatening latex allergy Editor There are two types of latex allergy; Type I reaction where IgE antibodies to natural rubber latex proteins potentially may cause anaphylactic reactions, and Type IV allergy to chemicals used in production as accelerators and antioxidants, which can cause allergic contact dermatitis.…”
Section: Editormentioning
confidence: 99%